2016
DOI: 10.1128/jvi.02497-15
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Free Assembly System for Generating Infectious Human Papillomavirus 16 Capsids Implicates a Size Discrimination Mechanism for Preferential Viral Genome Packaging

Abstract: We have established a cell-free in vitro system to study human papillomavirus type 16 (HPV16) assembly, a poorly understood process. L1/L2 capsomers, obtained from the disassembly of virus-like particles (VLPs), were incubated with nuclear extracts to provide access to the range of cellular proteins that would be available during assembly within the host cell. Incorporation of a reporter plasmid "pseudogenome" was dependent on the presence of both nuclear extract and ATP. Unexpectedly, L1/L2 VLPs that were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Similar results have been also described in humans, in which sequences of HPV were verified in blood and semen [54,55]. In addition, Cerqueira et al [47] currently demonstrated the cell-free assembly HPV-16 capsid. These results indicate the need to review the PVs natural history, as proposed by Munday [34].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar results have been also described in humans, in which sequences of HPV were verified in blood and semen [54,55]. In addition, Cerqueira et al [47] currently demonstrated the cell-free assembly HPV-16 capsid. These results indicate the need to review the PVs natural history, as proposed by Munday [34].…”
Section: Introductionsupporting
confidence: 69%
“…This occur because, according to the BPV natural history, the viral replication is dependent of cell differentiation [45][46][47]. Considering the paradigm of PVs replication cycle, the expression of capsid proteins (L1 and L2) and viral assembly are only verified in most differentiated epithelium layers (hypergranulous) [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…We noted that exogenous expression of E1 and E2 resulted in robust replication of HPV18 and hypothesized that this might increase packaging efficiency (though the resulting quasivirus could not be used to study early viral replication using the DpnI resistance assay, because the genomes would now be susceptible to DpnI digestion). The pMEP vectors used to express E1 and E2 are >10 kb in size and will not be packaged because they are above the 8-kb packaging limit (8, 46). Furthermore, despite the fact that E1 and E2 are expressed from the inducible metallothionein promoter, leaky expression ensures that they are expressed even in the absence of heavy metal induction (47).…”
Section: Resultsmentioning
confidence: 99%
“…A recent in vitro study suggested that papillomavirus genome incorporation may occur through a previously unrecognized size discrimination mechanism (Cerqueira et al, 2015). The viral capsid appears to undergo repeated rounds of assembly and disassembly in the cell nucleus sampling both cellular DNA loops and the viral genome.…”
Section: Papillomavirus Genome Packagingmentioning
confidence: 99%
“…To address this issue, we are in the process of developing strategies of producing the pseudovirions in cell-free systems in which high concentrations of purified L1/L2 protein and bacterially-derived peudogenome plasmids are used to drive the assembly reaction. In the first iteration, it was found that HPV16 L1/L2 proteins could generate high titers of peudovirions in the presence of purified bacterial plasmids, a nuclear extract and ATP (Cerqueira et al, 2015). In support of the size discrimination of genome packaging described above, assembly was efficient even when assembled VLPs were used in the reaction because the nuclear extracts were able to induce partial disassembly of the particles.…”
Section: Papillomavirus-based Gene Transfer Vectorsmentioning
confidence: 99%